2016
DOI: 10.1177/2048872616641281
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of decreased peripheral congestion detected by Bioelectrical Impedance Vector Analysis (BIVA) in patients hospitalized for acute heart failure: BIVA prognostic value in acute heart failure

Abstract: In AHF patients, an accurate physical examination evaluating the presence of rales and lower limbs oedema remains the cornerstone in the management of patients with AHF. A congestion reduction, obtained as a consequence of therapies and detected through BIVA analysis, with an increase of dR/H >11 Ω/m during hospitalization seems to be associated with increased 90 day survival in patients admitted for AHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
(55 reference statements)
0
22
0
4
Order By: Relevance
“…interstitial fluid status), which confirmed its prognostic role in our study. The literature has indicated that HI is a good 90-day (C-Index: 0.71) [10] and 1-year (C-Index: 0.72) [9] predictor of mortality in patients with AHF. Our findings confirmed the good diagnostic performance of this marker in predicting long-term mortality (C-Index 0.72) and identified a cut-off value of 73.8% (close to 74.3%, as reported by Núñez et al [11]).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…interstitial fluid status), which confirmed its prognostic role in our study. The literature has indicated that HI is a good 90-day (C-Index: 0.71) [10] and 1-year (C-Index: 0.72) [9] predictor of mortality in patients with AHF. Our findings confirmed the good diagnostic performance of this marker in predicting long-term mortality (C-Index 0.72) and identified a cut-off value of 73.8% (close to 74.3%, as reported by Núñez et al [11]).…”
Section: Tablementioning
confidence: 99%
“…However, the BNPs alone do not reflect pathophysiological pathways of congestion, and other markers of congestion might be useful in evaluating congestion and the risk stratification of HF patients. Among emerging techniques, BIVA has been demonstrated to be a simple and fast method for the assessment of body peripheral hydration status [6], providing prognostic information in HF patients [9][10][11]. Nevertheless, evidence also suggested that higher values of the BUN/Cr ratio are associated with "venous" congestion [7,12], and, in parallel, these values demonstrated prognostic impacts in HF patients independent of creatinine levels and glomerular filtration rate [7,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of BIVA in the prognosis of mortality of cardiac patients was demonstrated by Santarelli et al ,32 where they found that a resistance/height variation greater than 11 Ω/m from hospital admission to discharge was associated with greater acute heart failure survival, since BIVA plus clinical evaluation proved a predictive value (area under the curve (AUC) 0.97, p<0.0001) for adverse outcomes (rehospitalisation and death) at 90 days. Regarding the management of patients with acute heart failure at the ED, Di Somma et al 18 verified that BIVA correlates with brain natriuretic peptide (BNP), ultrasound IVC index and width, and that the combination of BIVA with BNP can support ED clinicians’ decision making about diuretic therapy.…”
Section: Discussionmentioning
confidence: 98%
“…En este sentido, se han propuesto diferentes definiciones para cuantificar de manera fiable la respuesta diurética, como la pérdida de peso en Kg por cada 40 mg i.v. de furosemida 66 , el uso de la ecografía pulmonar 9,10 o la impedanciometría 66,67 .…”
Section: Las Escalas De Descongestión Como Herramienta Terapéuticaunclassified